Roles of Major RNA Adenosine Modifications in Head and Neck Squamous Cell Carcinoma - Huo, Xing-xing; Wang, Shu-jie; Song, Hang; Li, Ming-de; Yu, Hua; Wang, Meng; Gong, Hong-xiao; Qiu, Xiao-ting; Zhu, Yong-fu; Zhang, Jian-ye (Frontiers in Pharmacology, 2021)
Head and neck squamous cell carcinoma (HNSCC) is the sixth most common cancer malignancy worldwide and is known to have poor prognosis. The pathogenesis behind the development of HNSCC is not fully understood. Modifications on RNA are involved in many pathophysiological processes, such as tumor development and inflammation. Adenosine-related RNA modifications have shown to be linked to cancer and may play a role in cancer occurrence and development. To date, there are at least 170 different chemical RNA modifications that modify coding and non-coding RNAs (ncRNAs). These modifications affect RNA stability and transcription efficiency. In this review, we focus on the current understanding of the four major RNA adenosine modifications (N6-Methyladenosine, N1-Methyladenosine, Alternative Polyadenylation Modification and A-to-I RNA editing) and their potential molecular mechanisms related to HNSCC development and progression. We also touch on how these RNA modifications affect treatment of HNSCCs.